THE INFLUENCE OF PARENTS' SOCIO-ECONOMIC STATUS AND SELF-EFFICIENCY ON THE INTEREST IN CONTINUE EDUCATION IN HIGHER EDUCATION IN SMA STUDENTS IN CENGKARENG DISTRICT. - Navari, Ravita Gesit; Faslah, Roni; Karyaningsih, RR Ponco Dewi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
The purpose of this study was to determine the Socio-Economic Status of Parents and Self-Efficacy on Interest in Continuing Education in Higher Education in High School Students, Cengkareng District. The research method that the researcher uses is a survey method with a descriptive approach, the population used is class XII SMA Cengkareng Subdistrict with a sample of 165 with a population of 110 students. The analysis technique used in this study uses the SEM (Structural Equation Modeling) model which is operated by SmartPLS version 3.0 program for hypothesis testing. The results obtained are that the socioeconomic status of parents has a positive and significant effect on the interest in continuing to college, self-efficacy has a positive and significant effect on the interest in continuing to college, the socio-economic status of parents and self- efficacy have a simultaneous effect on the interest in continuing to college.